Don't Puff, Pal - Er, Jolene (Nanyang Technological University, 2023)
Don’t Puff, Pal is a youth-centric health communication campaign aimed at raising awareness about the harmful health effects of vaping among university students aged 21 to 27 years old. It was aimed at increasing their willingness to share about the harmful effects of vaping with peers, in order to shape negative perceptions and social norms around vaping in Singapore. E-cigarettes, also commonly known as vapes, have been increasingly popularised in recent years, especially among the younger Singaporeans. Despite the ban in Singapore, almost 5,000 users were caught purchasing, using or possessing vapes in 2021, with the numbers spiking prominently during the COVID-19 pandemic. Recognising the significant impact of peer influence on youths, the campaign sought to use peer pressure for good and empower university students with the necessary knowledge they can share with their fellow peers. Guided by the Theory of Planned Behaviour (TPB), the campaign employed a comprehensive approach which consisted of posting trendy and relatable social content such as short-form videos and shareable bite-sized infographics. The campaign culminated with an on-ground campus roadshow to interact with our audience. This paper seeks to examine the underlying factors motivating vape usage among local youths and vape-related information sharing, using the three constructs of the TPB as a guiding framework. The paper also delves into the post-campaign evaluation of impact and output objectives, limitations and future recommendations.